Constitutional Politics in the European Union - Castiglione, D. author. aut Link
XII, 292 p.
Keywords: This volume examines the 'Convention on the Future of Europe' as a moment of European constitutional politics. It discusses the contested nature of constitutional politics in the EU, and how the Convention dealt with these issues. The book also assesses the Convention's aftermath.